Length‐weight relationship of Thryssa malabarica (Bloch, 1795) and Thryssa dayi Wongratana, 1983 from Kerala, southwest coast of India. (1st August 2017) - Roul, S. K.; Retheesh, T. B.; Prakasan, D.; Abdussamad, E. M.; Rohit, P.
Summary: The present study reports the length‐weight relationships (LWRs) of two clupeoid fish species, Thryssa malabarica (Bloch, 1795) and Thryssa dayi Wongratana, 1983 from Kerala waters, southwest coast of India during the period October 2015 to September 2016. Altogether 88 specimens of T. malabarica and 97 T. dayi were collected on weekly basis from gill nets (mesh size, 2.6–5.0 cm) and ring seines (mesh size, 0.8–2.6 cm) during the period. The value of parameter b in the equation of LWRs was estimated as 3.237 and 3.248 for T. malabarica and T. dayi respectively.